Item Analysis of Creative Thinking Skills Using Rasch Modelling in the Ethnozoology of Traditional Foods - Alif Yanuar Zukmadini; Kasrina Kasrina; Abdul Rahman Singkam; Abas Abas; Ayu Sulistiawati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Prospective biology teachers need creative thinking skills to address biodiversity issues, such as traditional food practices. Measuring these skills requires valid, reliable, and appropriate instruments. This study evaluated a creative thinking skills instrument in traditional food ethnozoology using the Rasch model. Employing a quantitative descriptive method, the instrument contains 15 multiple-choice questions based on six creative thinking indicators: curiosity, fluency, originality, elaboration, imagination, and flexibility. A pilot test involved 45 prospective biology teachers. Data were analyzed with the Winsteps application to assess item difficulty, item fit, bias detection (DIF), and reliability. Results showed item difficulty ranged from ±3.69 logits, with two items rated as difficult and three as easy. Thirteen items fit well, one was borderline, and one required revision. DIF analysis showed no significant gender bias. Item reliability was 0.86 (good), person reliability was 0.63 (poor), and Cronbach's alpha was 0.71 (fair). The instrument meets validity and reliability criteria, but adding more difficult items may improve its discrimination among high-ability respondents. Thus, the instrument can be used to diagnose creative thinking skills specifically related to traditional food ethnozoology in prospective biology teachers, helping to identify areas for further development.